Sr90-CA SEPARATION IN SAMPLES OF MILK. PART ONE - Rivera C., Dolores (2001)
It is shown a chemical method to separate Sr90/Ca/Ba from milky samples in order to reduce expenses. The separation of Ca from Sr90/Ba is carried out in ethanol. Ca is evaluated by permanganometry method while the Ba is separated as BaCrO4 and the Sr90 is precipitated as oxalate. The recovery of Sr90 is done by using a trace trailing of Sr85 which is quantified by spectrornetry. The result of the first part shows a chemical recovery of between 79 - 80% and the separation factors are equivalent to 1.